Taxonomic revision and species delimitation of coccoid green algae currently assigned to the genus Dictyochloropsis (Trebouxiophyceae, Chlorophyta). Issue 4 (15th June 2016) - Škaloud, Pavel; Friedl, Thomas; Hallmann, Christine; Beck, Andreas; Dal Grande, Francesco
Abstract : Coccoid green algae traditionally classified in Dictyochloropsis have a complex, reticulate chloroplast, when mature, without a pyrenoid. They occupy remarkably diverse ecological niches as free‐living organisms or in association with lichen‐forming fungi and were recently shown to form two distinct lineages within Trebouxiophyceae. We used a polyphasic approach to revise the taxonomy of the genus. Based on phylogenetic analysis of the 18S rRNA gene, and detailed morphological investigation using comparative conventional light and confocal microscopy, we have assigned these lineages to two genera, Dictyochloropsis and Symbiochloris gen. nov. We have reconsidered the diagnostic generic features as follows: Dictyochloropsis comprises only free‐living algae with a reticulate chloroplast, forming lobes in a parallel arrangement at some ontogenetic stages, and which reproduce only by means of autospores. This agrees with Geitler's original diagnosis of Dictyochloropsis, but not with the later emendation by Tschermak‐Woess. Consequently, the species of Dictyochloropsis sensu Tschermak‐Woess are assigned to Symbiochloris, with new combinations proposed. Symbiochloris encompasses free‐living and/or lichenized algae with lobed chloroplasts and that reproduce by forming zoospores characterized by two subapical isokont flagella that emerge symmetrically near the flattened apex. In addition, using coalescent‐based approaches, morphological characters and secondary structure of ITS transcripts, we inferred species boundaries and taxonomic relationships within the newly proposed genera. Two species of Dictyochloropsis and nine species of Symbiochloris are delimited, including the newly described species D. asterochloroides, S. handae, S. tropica, and S. tschermakiae . Our results further support the non‐monophyly of autosporine taxa within Trebouxiophyceae.